Mix Codes in Conversations of Banggai Laut Students in Palu City - Ufara Dzikri; Syamsuddin Syamsuddin; Julia Marfuah; Mohammad Tahir; Ulfah Ulfah (Global Education Journal, 2026)
This diversity makes Indonesia one of the countries with a high level of multilingualism, where people are used to using more than one language in their daily lives. The purpose of this study is to describe the form of code mixing used in the conversation of Banggai Laut students in Palu City and to analyze the factors that cause code mixing in the conversation of Banggai Laut students in Palu city. This research is a qualitative descriptive research. The research place is located at the location of the Banggai Laut Student Dormitory, Tondo, East Palu. Data collection is carried out by four techniques, namely observation, recording, listening, and recording. This research was sourced from students from Banggai Laut in informal conversations such as gathering in the Banggai Laut student dormitory environment. The results of this study found that there are four forms of code mixing in the conversation of Banggai Laut students, namely mixing code in the form of basic words, repetitions, phrases and clauses. The cause of code mixing is the habit of speakers in using regional languages and terms from foreign languages.